2011
DOI: 10.33151/ajp.9.1.37
|View full text |Cite
|
Sign up to set email alerts
|

The Exploration of Physical Fatigue, Sleep and Depression in Paramedics: A Pilot Study

Abstract: Introduction Ambulance paramedics are members of a discipline that forms a unique part of the emergency services. As pre-hospital providers they are constantly and increasing faced with heavy workloads that are physically, mentally and emotionally tiring. Fatigue and sleep disturbance are factors which can compromise the effectiveness of these workers, and as a result not only hamper patient safety but can have detrimental consequences on the paramedics‟ health and overall well-being. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(80 citation statements)
references
References 48 publications
6
70
0
4
Order By: Relevance
“…23 Sofianopoulos et al found that "almost half of paramedic (respondents) answered yes to having nodded off or fallen asleep whilst driving". 27 Studnek and Fernandez found that the two variables associated with increased risk of ambulance collision were young age and fatigue. 28 Gender-Fifty-three percent of the cases in this study involved females, yet females make up just 27% of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…23 Sofianopoulos et al found that "almost half of paramedic (respondents) answered yes to having nodded off or fallen asleep whilst driving". 27 Studnek and Fernandez found that the two variables associated with increased risk of ambulance collision were young age and fatigue. 28 Gender-Fifty-three percent of the cases in this study involved females, yet females make up just 27% of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Australian ambulance personnel play a key role in the Australian health system, providing clinical care and specialised transport . However, there is significant evidence of high levels of stress, fatigue and the frequent experience of emotionally traumatic events for this population . These risks have primarily been categorised for metropolitan ambulance personnel, while rural and regional ambulance personnel in Australia have been largely overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research reveals that paramedic fatigue is associated with worker burnout and attrition, sick leave and work disability, health complaints, such as headaches and gastrointestinal illness, depression, anxiety and stress . Paramedic fatigue also impacts upon operational performance and patient and public safety.…”
Section: Introductionmentioning
confidence: 99%
“…Paramedic fatigue also impacts upon operational performance and patient and public safety. In one study, 88% of a sample of paramedics reported experiencing fatigue that affected their work performance and almost half of the respondents reported falling asleep while driving . Difficulty remembering emergency service protocol, difficulty operating the ambulance and increased risk of being involved in an ambulance accident have also been identified as a result of paramedic fatigue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation